ØªØ·ÙˆÙŠØ± Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø¨Ù†Ø¸Ø§Ù… Ø§Ù„Ø¥Ù†Ø¬Ù„ÙŠØ²ÙŠØ© Ø¨Ø¯ÙˆÙ† ØµØ¹ÙˆØ¨Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… ØªØ·Ø¨ÙŠÙ‚ Ø£Ù†Ø¯Ø±ÙˆÙŠØ¯ Ù„Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… - Robby Arinil Asror; Halil Thahir; Mokhammad Miftakhul Huda (Lughawiyah: Journal of Arabic Education and Linguistics, 2020)
Ø£Ù‡Ø¯Ø§Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù„Ø¥Ù†ØªØ§Ø¬ Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø¨Ù†Ø¸Ø§Ù… Ø§Ù„Ø¥Ù†Ø¬Ù„ÙŠØ²ÙŠØ© Ø¨Ø¯ÙˆÙ† ØµØ¹ÙˆØ¨Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… ØªØ·Ø¨ÙŠÙ‚ Ø£Ù†Ø¯Ø±ÙˆÙŠØ¯ Ù„ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙÙ‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙˆÙ„Ù…Ø¹Ø±ÙØ© ØªØµØÙŠØ Ø§Ù„Ù…Ù†ØªØ¬ Ùˆ Ù„Ù…Ø¹Ø±ÙØ© Ù†Ù…ÙˆØ°Ø Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…Ù†Ø§Ø³Ø¨ Ù„ØªØ·Ø¨ÙŠÙ‚ Ø§Ù„Ù…Ù†ØªØ¬. ÙˆÙŠØ³ØªØ®Ø¯Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¨Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„ØªØ·ÙˆÙŠØ± Ù…Ù† Ø¯ÙŠÙƒ ÙˆÙƒØ§Ø±ÙŠ. Ø§Ù„Ù…Ù†ØªØ¬ Ø§Ù„Ù…Ø·ÙˆØ± Ù‡Ùˆ ØªØ·Ø¨ÙŠÙ‚ Ø£Ù†Ø¯Ø±ÙˆÙŠØ¯ ÙŠØ³Ù…Ù‰ Ø¨Ù€Ù€Ù€Ù€"Ø³Ù‡Ù„Ø©"ØŒ ÙÙŠÙ‡ Ø«Ù„Ø§Ø«Ø© Ù…ÙˆØ¶ÙˆØ¹Ø§Øª ÙˆÙ‡ÙŠ: Ø§Ù„Ø£Ø³Ø±Ø©ØŒ Ùˆ Ø§Ù„ØªØ¹Ø§Ø±ÙØŒ Ùˆ Ø¨ÙŠØªÙŠ. Ùˆ Ù„ÙƒÙ„ Ù…ÙˆØ¶ÙˆØ¹ Ø£Ø±Ø¨Ø¹Ø© Ù…ÙƒÙˆÙ†Ø§Øª Ø¹Ù„Ù‰ Ø§Ù„Ø£Ù‚Ù„ØŒ Ù…Ù†Ù‡Ø§ Ø§Ù„Ù†Øµ Ùˆ Ø§Ù„ÙÙ‰Ø¯ÙŠÙˆ Ùˆ Ø§Ù„Ù‚ØµØ© Ø§Ù„Ù‚ØµÙŠØ±Ø© ÙˆØ§Ù„Ù…ÙØ±Ø¯Ø§Øª. Ù†ØªÙŠØ¬Ø© ØªØµØÙŠØ Ø§Ù„Ù…Ù†ØªØ¬ Â ØªØ¯Ù„ Ø¹Ù„Ù‰ Ø£Ù† Ø§Ù„Ù†ØªÙŠØ¬Ø© Ù…Ù† Ø®Ø¨ÙŠØ± Ø§Ù„Ù…Ø§Ø¯Ø© Ù‡ÙŠ 80.5% ÙÙ‰ ÙØ¦Ø© Ø¬ÙŠØ¯Ø© Ùˆ Ø§Ù„Ù†ØªÙŠØ¬Ø© Ù…Ù† Ø®Ø¨ÙŠØ± Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ù‡ÙŠ 86.1% ÙÙ‰ ÙØ¦Ø© Ø¬ÙŠØ¯Ø© Ø£ÙŠØ¶Ø§ØŒ Ùˆ Ø§Ù„Ù†ØªÙŠØ¬Ø© Ù…Ù† Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ù…ÙŠØ¯Ø§Ù†ÙŠ Ù…Ù† Ø§Ù„Ù…Ø¹Ù„Ù… Ù‡ÙŠ 85% Ùˆ Ù…Ù† Ø§Ù„Ø·Ù„Ø§Ø¨ 83.3% ÙÙ‰ ÙØ¦Ø© Ø¬ÙŠØ¯Ø© Ø£ÙŠØ¶Ø§. Ø£Ù…Ø§ Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…Ù†Ø§Ø³Ø¨ Ù„ØªØ·Ø¨ÙŠÙ‚ Ø§Ù„Ù…Ù†ØªØ¬ Ø§Ù„Ù…Ø·ÙˆØ± Ù‡Ùˆ Ø§Ù„ØªØ¹Ù„Ù… Ø¨Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„Ù…Ø³ØªÙ‚Ù„.The purposes of this study were to produce an effortless English system instructional media using android application to improve speaking skills in Arabic, to determine the feasibility of the developed product, and to find out the appropriate learning model to implement the product. This study used Dick and Carry development model. The developed product was an application called Sahla which has several themes, namely: Family, Introduction, and My Home. Each theme has at least four components, including reading text, video, short story, and vocabulary. The results of product validation described the instructional expertâ€™s judgment was 80.5% in the good category and the media expert gave 86.1% in the good category too, while the field test given to teachers was 85% and to students was 83.3% in the good category too. The appropriate learning model to implement the developed product was self-learning model.